Ozone promotes macrophage efferocytosis and alleviates neuropathic pain by activating the AMPK/Gas6-MerTK/SOCS3 signaling pathway - Ruan, Shirong; Jia, Rumeng; Hu, Liang; Liu, Yuge; Tian, Qingyan; Jiang, Kunmao; Xia, Xinyue; Tao, Xueyou; Liu, Wen-Tao; Pan, Yinbing; Hu, Fan (Frontiers in Immunology, 2024)
BackgroundNeuropathic pain (NPP) is a multifaceted pain syndrome that occurs as a consequence of physical injury or underlying diseases, with an incidence rate of 7%-10%, NPP poses a significant clinical challenge as current treatment options are ineffective. The accumulation of apoptotic cells and neuroinflammation play crucial roles in the pathological mechanisms of NPP. Here, we aim to investigate strategies for effectively clearing apoptotic cells and provide therapeutic interventions for NPP.MethodsCCI mice were treated with different concentrations of ozone (15μg, 30μg, 45μg) to investigate the effects on the accumulation of apoptotic cells and neuroinflammation. In vitro, the phagocytic function of BMDM towards apoptotic neutrophils after ozone treatment was examined.ResultsWe found ozone at a concentration of 30μg significantly alleviated mechanical hypersensitivity in CCI mice and ozone significantly upregulates the phagocytic activity of BMDM. Furthermore, we investigated the mechanisms and found ozone could activate AMPK, upregulate Gas6 (but not Protein S), activate MerTK (a key receptor involved in apoptosis), and enhance the phagocytic function of BMDM towards apoptotic neutrophils. It caused the promotion of SOCS3 expression and the suppression of inflammatory factors IL-1β, IL-6, and TNF-a. Interestingly, the effect of ozone in alleviating CCI-induced pain was abolished by the AMPK inhibitor CC and the MerTK receptor inhibitor UNC2541.ConclusionOzone facilitated macrophage clearance of apoptotic cells, decreased neuroinflammation by activation of p-AMPK/Gas6/MerTK/SOCS3 signaling pathway, which may become an effective therapeutic approach for neuropathic pain after further clinical validation.